Thực hiện phép chia
1, \(3x^4-2x^3-2x^2+4x-8:x^2-2\)
2,\(2x^3-26x-24:x^2+4x+3\)
Thực hiện phép tính:
a. (19x^2-14x^3+9-20x+2x^4) : (1+x^2-4x)
b. (3x^4-2x^3-2x^2+4x+8) : x^2-2
c. (2x^3-26x-24) : (x^2+4x+3)
Giúp mình với mn ơi :(((
làm phép chia
1) (x^6 - 2x^4 + 6x^3 - 4x^2) : 6x^2
2) (-2x^5 = 3x^2 - 4x^3) : 2x^2
3) (15x^3 - 10x^2 + x - 2) : (x - 2)
4) (2x^4 -3x^3 - 3x^2 + 6x - 2) : (x^2 - 2)
Thực hiện phép chia:
1. (-3x3 + 5x2 - 9x + 15) : ( 3x + 5)
2. ( 5x4 + 9x3 - 2x2 - 4x - 8) : ( x-1)
3. ( 5x3 + 14x2 + 12x + 8 ) : (x + 2)
4. ( x4 - 2x3 + 2x -1 ) : ( x2 - 1)
5. ( 5x2 - 3x3 + 15 - 9x ) : ( 5 - 3x)
6. ( -x2 + 6x3 - 26x + 21) : ( 3 -2x )
1: Sửa đề: 3x-5
\(=\dfrac{-x^2\left(3x-5\right)-3\left(3x-5\right)}{3x-5}=-x^2-3\)
2: \(=\dfrac{5x^4-5x^3+14x^3-14x^2+12x^2-12x+8x-8}{x-1}\)
=5x^2+14x^2+12x+8
3: \(=\dfrac{5x^3+10x^2+4x^2+8x+4x+8}{x+2}=5x^2+4x+4\)
4: \(=\dfrac{\left(x^2-1\right)\left(x^2+1\right)-2x\left(x^2-1\right)}{x^2-1}=x^2+1-2x\)
5: \(=\dfrac{x^2\left(5-3x\right)+3\left(5-3x\right)}{5-3x}=x^2+3\)
Chủ đề 1: Thực hiện phép tính
1) (2x+3).(2x-3)-4x.(x+5)
2) 6/x2 - 9 + 5/x-3 + 1/x+3
3)5x.(x-3)+(x-2)2
4) 4x/x+2 - 3x/x-2 + 12x/ x2 - 4
5) x(x+2) - ( x-3)(x+3)
6) 1/3x-2 + -4/3+2 + 6-3x/9x2 - 4
7)2x.(3x-1)+(x+2)2
8) 6/x+3 - 6/x-3 + 9x+9/x2 - 9
9) (2x - 5)2 - x(4x-13)
10) x-1/x + 4/x+8 + 8/x2 + 8x
11) (2x+1)2 + (x-5)(x+5)-x(5x+7)
12) 6/x2-9 + 5/x-3 + 1/x+3
13) 6x(5x-2)+(2x+3)2
14) x/x-2 + -2/x-3 + x(1-x)/x2-9
15) (x-2)2-x(x+5)
16) 2/x+3 + 3/x-3 + -6/x2-9
17) 3x(x-3) + (3x-1)2
\(\left(2x+3\right)\left(2x-3\right)-4x\left(x+5\right)=4x^2-9-4x^2-20x=-20x-9\)
\(5x\left(x-3\right)+\left(x-2\right)^2=5x^2-15x+x^2-4x+4=6x^2-19x+4\)
\(x\left(x+2\right)-\left(x-3\right)\left(x+3\right)=x^2+2x-\left(x^2-9\right)=x^2+2x-x^2+9=2x+9\)
Thực hiện phép tính chia
a. (6x3 + 3x2 + 4x + 2) : (3x2 + 2)
b. (2x3 - 26x - 24) : (x2 + 4x + 3)
c. (x3 - 7x + 6) : (x + 3)
a) 6x3 + 3x2 + 4x + 2
= ( 6x3 + 3x2 ) + ( 4x + 2 )
= 3x2( 2x + 1 ) + 2( 2x + 1 )
= ( 2x + 1 )( 3x2 + 2 )
=> ( 6x3 + 3x2 + 4x + 2 ) : ( 3x2 + 2 ) = 2x + 1
b) 2x3 - 26x - 24
= 2( x3 - 13x - 12 )
= 2( x3 + 4x2 - 4x2 + 3x - 16x - 12 )
= 2[ ( x3 + 4x2 + 3x ) - ( 4x2 + 16x + 12 ) ]
= 2[ x( x2 + 4x + 3 ) - 4( x2 + 4x + 3 ) ]
= 2( x2 + 4x + 3 )( x - 4 )
=> ( 2x3 - 26x - 24 ) : ( x2 + 4x + 3 ) = 2( x - 4 ) = 2x - 8
c) x3 - 7x + 6
= x3 - 3x2 + 3x2 + 2x - 9x - 6
= ( x3 - 3x2 + 2x ) + ( 3x2 - 9x + 6 )
= x( x2 - 3x + 2 ) + 3( x2 - 3x + 2 )
= ( x2 - 3x + 2 )( x + 3 )
=> ( x3 - 7x + 6 ) : ( x + 3 ) = x2 - 3x + 2
a,\(\left(6x^3+3x^2+4x+2\right)\div\left(3x^2+2\right)\)
\(=\left[3x^2\left(2x+1\right)+2\left(2x+1\right)\right]\div\left(3x^2+2\right)\)
\(=\left[\left(3x^2+2\right)\left(2x+1\right)\right]\div\left(3x^2+2\right)\)
\(=2x+1\)
Thực hiện phép chia
a. (6x3 + 3x2 + 4x + 2) : (3x2 + 2)
b. (2x3 - 26x - 24) : (x2 + 4x + 3)
c. (x3 - 7x + 6) : (x + 3)
Thực hiện phép tính chia
a. (6x3 + 3x2 + 4x + 2) : (3x2 + 2)
b. (2x3 - 26x - 24) : (x2 + 4x + 3)
c. (x3 - 7x + 6) : (x + 3)
Thực hiện phép chia
a. (6x3 + 3x2 + 4x + 2) : (3x2 + 2)
b. (2x3 - 26x - 24) : (x2 + 4x + 3)
c. (x3 - 7x + 6) : (x + 3)
Thực hiện phép chia
a. (6x3 + 3x2 + 4x + 2) : (3x2 + 2)
b. (2x3 - 26x - 24) : (x2 + 4x + 3)
c. (x3 - 7x + 6) : (x + 3)